2004
DOI: 10.1111/j.1601-5223.1999.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Rabbit Microsatellite Primers for Studies of Hybridisation between an Introduced and a Native Hare Species

Abstract: Introduced species may hybridise with relatives in the native fauna or flora and thereby compete for matings and transmit alien DNA. Such interference may contaminate unique genepools, disturb existing ecological balances and may ultimately result in the extinction of the native species. In Sweden, the introduced brown hare (Lepus europaeus Pall.) hybridise with the native mountain hare (L. timidus L.), both relatively common members of the present Swedish fauna. This hybridisation has resulted in the transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…First results from microsatellites, however, do not look very convincing. While Andersson et al (1999) did not find diagnostic microsatellite loci for distinguishing L. europaeus and L. timidus from Sweden, Estonba et al (2006) claimed to have shown a distinction among three Iberian hare species (i.e., L. europaeus, Lepus granatensis, Lepus castroviejoi) with six microsatellite loci. But their cluster (NJ) analysis (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…First results from microsatellites, however, do not look very convincing. While Andersson et al (1999) did not find diagnostic microsatellite loci for distinguishing L. europaeus and L. timidus from Sweden, Estonba et al (2006) claimed to have shown a distinction among three Iberian hare species (i.e., L. europaeus, Lepus granatensis, Lepus castroviejoi) with six microsatellite loci. But their cluster (NJ) analysis (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Highly variable nuclear DNA markers, such as microsatellite loci, would be desirable for cross checking particularly in regions that are under suspicion of harboring mtDNA introgression among hares, but are currently not elaborated. A microsatellite approach based on five loci did not succeed in unambiguously identifying hybrids of brown and mountain hares (L. europaeus and L. timidus) in southern Scandinavia (see [4]). Application of more loci might produce alleles that are diagnostic for several hare species, or might, in combination with appropriate statistics, enable population assignment.…”
Section: Discussionmentioning
confidence: 98%
“…Three of these (Sat5, Sat12, Sat13) were isolated in rabbit (Mougel et al 1997) but gave good results in hare, too (Andersson et al 1999;Thulin et al 2006). Remaining five microsatellite loci (Lsa1, Lsa2, Lsa3, Lsa6, Lsa8) were identified in L. capensis by Kryger et al (2002) and used in several hare population genetic studies (Thulin et al 2006).…”
Section: Methodsmentioning
confidence: 98%